Recognition of protein apparently specific to odontogenic keratocyst fluids. - Douglas, C W (1986)
Separate antisera were raised against keratocyst, dentigerous cyst, and radicular cyst fluids and used to analyse a range of fluids from cysts of known type. Samples were subjected to crossed immunoelectrophoresis into homologous antiserum through an intermediate gel containing antibody to whole human serum to screen out serum derived components. A major antigen, designated X, which seems to be of epithelial origin but is not a keratin, was identified in keratocyst fluids. X resolves as two bands on sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) with molecular weights of 81 K and 89 K and its major antigenic epitope is associated with disulphide bonds. Of the cysts studied to date, antigen X has been found consistently and exclusively in fluids from keratocysts; its presence and detection is independent of total soluble protein concentration and thus offers real potential as a reliable marker for preoperative diagnosis.